Perbandingan Fonologi Bahasa Indonesia Dan Bahasa Jawa - Ayu Sena; Salwa Nurhomilatul W.N; Sintia Putri (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This article discusses the comparison of Indonesian and Javanese phonology using descriptive qualitative methods by conducting analysis and comparison. The data observed is linguistic data which contains vowel and consonant elements in Indonesian and Javanese. Vowels are related to the height of the tongue, the movement of the tongue, strictures, and the shape of the lips. In comparative language science, Indonesian and Javanese have differences and similarities between them. One of the similarities is in the vowel phonemes. Both Indonesian and Javanese have five basic vowels, namely /a/, /i/, /u/, /e/, and /o/. Indonesian and Javanese also have 10 consonants, namely bilabial, labio-dental, apico-dental, apico-alveolar, apico-palatal, lamino-alveolar, lamino-palatal, medio-palatal, dorso-velar, and laryngeal.